Hot-rolling production method of super high strength and toughness steel with tensile strength of more than 980mpa and super high strength and toughness steel
Patent Information
- Application Number
- CN202611199518.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-07
- Publication Date
- 2026-10-27
AI Technical Summary
[0014]本申请实施例通过综合调整工艺链,各步骤参数相互协同,最终实现产品厚度2.0-12.0mm、抗拉强度≥980MPa、-40℃夏比冲击功≥60J的性能,满足商用车轻量化与常规加工工艺需求。
Abstract
Description
Technical Field
[0001] This application relates to the field of iron and steel metallurgy technology, and in particular to a hot rolling production method for ultra-high strength and toughness steel with a tensile strength ≥980MPa and the ultra-high strength and toughness steel itself. Background Technology
[0002] As a core load-bearing component, the chassis beam of a commercial vehicle directly determines the load-bearing capacity, fatigue resistance, and driving safety of the vehicle frame. Its performance requirements are constantly increasing with the trends of heavier loads, higher speeds, and new energy vehicles in the commercial vehicle industry. Currently, lightweighting in the automotive industry has become a global consensus. It is not only a key path to reduce fuel consumption and exhaust emissions, but also a core requirement for improving the driving range and optimizing the overall energy efficiency of new energy commercial vehicles. Material upgrading is the most direct and effective technological direction for achieving lightweighting.
[0003] Developing a production method that is stable, cost-controllable, and lightweight has become an urgent technical problem to be solved in this field. Summary of the Invention
[0004] This application provides a hot-rolling production method for ultra-high strength and toughness steel with a tensile strength ≥980MPa and the ultra-high strength and toughness steel itself, which meets the requirements of lightweighting and conventional processing technology for commercial vehicles.
[0005] In a first aspect, this application provides a hot-rolling production method for ultra-high strength and toughness steel with a tensile strength ≥980MPa, comprising the following steps: obtaining a slab to be hot-rolled; feeding the slab to be hot-rolled into a heating furnace at a temperature ≥600℃ to heat the slab to obtain a heated slab; wherein the heating process includes a preheating section, a heating section, and a soaking section, controlling the soaking section time to ≥30min, and the furnace exit temperature to be 1220-1260℃; performing rough descaling on the heated slab and then rough rolling it, wherein a heat insulation cover is used during the rough rolling process to obtain an intermediate slab; In the roughing process, 5 or 7 passes are used for rolling, with a final rolling temperature of 1080-1150℃ and an intermediate slab thickness of 40-50mm. The intermediate slab is then finished to obtain a hot-rolled coil. During the finishing process, descaling is performed simultaneously. The finishing mill inlet temperature is 950-1080℃, and the finishing mill outlet temperature is 850-920℃. The hot-rolled coil is cooled using an ultra-fast cooling and front-end centralized cooling mode to obtain the hot-rolled finished product. The hot-rolled finished product is then coiled to obtain ultra-high strength and toughness steel at a coiling temperature of 520-580℃.
[0006] According to an embodiment of the first aspect of this application, the total furnace time of the heating process is controlled to be 150-350 min.
[0007] According to an embodiment of the first aspect of this application, the preheating section includes heating the slab to be heated to 800-1000°C at a rate of 0.05-0.15 min / °C; the heating section has a heating rate of 0.12-0.20 min / °C; and the soaking section lasts for 23-60 min.
[0008] According to an embodiment of the first aspect of this application, the pressure of the coarse descaling treatment is ≥18MPa.
[0009] According to an embodiment of the first aspect of this application, the use of a hot coil box for heat preservation and conveying of intermediate slabs is selected based on the rolling specifications.
[0010] According to an embodiment of the first aspect of this application, the pressure of the fine descaling treatment is ≥18MPa.
[0011] According to an embodiment of the first aspect of this application, the hot-rolled slab comprises the following components by mass fraction: C 0.15 wt% to 0.17 wt%, Mn 1.15 wt% to 1.35 wt%, Si 0.10 wt% to 0.25 wt%, Nb 0.02 wt% to 0.04 wt%, V 0.03 wt% to 0.05 wt%, Ti 0.01 wt% to 0.25 wt%, Mo 0.20 wt% to 0.40 wt%, Cr 0.30 wt% to 0.50 wt%, S ≤ 0.005 wt%, P ≤ 0.015 wt%, Alt 0.015 to 0.06 wt%, B 0.0008-0.0015%, with the remainder being Fe and unavoidable impurity elements.
[0012] According to an embodiment of the first aspect of this application, the thickness of the ultra-high strength and toughness steel is 2.0-12.0 mm, and the Charpy impact energy at -40℃ is ≥60 J.
[0013] Secondly, this application provides an ultra-high strength and toughness steel with a tensile strength ≥980MPa, which is prepared by the production method of the first aspect of this application. The ultra-high strength and toughness steel has a thickness of 2.0-12.0mm, a tensile strength ≥980MPa, and a Charpy impact energy ≥60J at -40℃.
[0014] This application embodiment achieves product performance of 2.0-12.0mm thickness, tensile strength ≥980MPa, and Charpy impact energy ≥60J at -40℃ by comprehensively adjusting the process chain and coordinating the parameters of each step, thus meeting the requirements of lightweighting and conventional processing technology for commercial vehicles. Detailed Implementation
[0015] The various embodiments or implementation schemes in this specification are described in a progressive manner, with each embodiment focusing on the differences from other embodiments.
[0016] In the description of this specification, the references to terms such as "one embodiment," "some embodiments," "illustrative embodiment," "example," "specific example," or "some examples," etc., indicate that a specific feature, structure, material, or characteristic described in connection with an embodiment or example is included in at least one embodiment or example of this application. In this specification, the illustrative expressions of the above terms do not necessarily refer to the same embodiment or example. Furthermore, the specific features, structures, materials, or characteristics described may be combined in any suitable manner in one or more embodiments or examples.
[0017] Furthermore, the terms "first" and "second" are used for descriptive purposes only and should not be construed as indicating or implying relative importance or implicitly specifying the number of technical features indicated. Thus, a feature defined as "first" or "second" may explicitly or implicitly include at least one of that feature. In the description of this application, "multiple" means at least two, such as two, three, etc., unless otherwise explicitly specified.
[0018] The mainstream commercial vehicle frame currently uses 355-700MPa high-strength steel to manufacture core components such as transverse and longitudinal beams. However, this strength grade of steel is approaching its performance bottleneck: if the weight reduction effect is further pursued by simply thinning the thickness, the fatigue resistance and impact resistance of the frame will be significantly reduced, which will not meet the needs of commercial vehicles under long-term heavy loads and complex road conditions.
[0019] To overcome this limitation, ultra-high strength steel of 900MPa and above is used in the manufacture of the main beam. Theoretically, this can achieve a weight reduction of more than 15% while taking into account the fatigue performance of the frame. Developing a production method that is stable, cost-controllable, and can achieve lightweighting has become an urgent technical problem to be solved in this field.
[0020] In view of the above problems, this application provides a hot rolling production method for ultra-high strength and toughness beam steel with a tensile strength ≥980MPa, which can significantly reduce the thickness of the plate without reducing the structural strength, thereby achieving lightweighting.
[0021] This application provides a hot-rolling production method for ultra-high strength and toughness steel with a tensile strength ≥980MPa, comprising the following steps: obtaining a slab to be hot-rolled; feeding the slab to be hot-rolled into a heating furnace at a temperature ≥600℃ to heat the slab to obtain a heated slab; wherein the heating process includes a preheating section, a heating section, and a soaking section, controlling the soaking section time to ≥30min, and the furnace exit temperature to be 1220-1260℃; performing rough descaling on the heated slab and then rough rolling to obtain an intermediate slab; wherein the rough rolling adopts 5 or 7 passes. The final rolling temperature is 1080-1150℃. During rough rolling, an insulation cover is used, and the thickness of the intermediate slab is 40-50mm. The intermediate slab is then finished rolled to obtain a hot-rolled coil. Fine descaling is performed simultaneously during the finish rolling process. The finish rolling inlet temperature is 950-1080℃, and the finish rolling outlet temperature is 850-920℃. The hot-rolled coil is cooled using an ultra-fast cooling and front-end centralized cooling mode to obtain the hot-rolled finished product. The hot-rolled finished product is coiled to obtain ultra-high strength and toughness steel at a coiling temperature of 520-580℃.
[0022] In this embodiment, the hot-rolled slab must be a qualified alloy slab, and its chemical composition design must be adapted to the strengthening requirements of ultra-high strength and toughness steel. Furthermore, the slab must be free of metallurgical defects such as shrinkage cavities and excessive inclusions. If the slab has quality problems, it will directly lead to defects such as cracks and delamination in the subsequent rolling process, making it impossible to achieve the target strength and toughness.
[0023] The alloy composition of the hot-rolled slab is a prerequisite for fine grain strengthening and precipitation strengthening. During the heating, rolling and cooling process, microalloying elements will work together with the process parameters through solid solution, precipitation and other behaviors to finally achieve a tensile strength of ≥980MPa, which is suitable for the heavy load and low temperature working conditions of commercial vehicle beams.
[0024] In some embodiments, the hot-rolled slab comprises the following components by mass fraction: C 0.15 wt% to 0.17 wt%, Mn 1.15 wt% to 1.35 wt%, Si 0.10 wt% to 0.25 wt%, Nb 0.02 wt% to 0.04 wt%, V 0.03 wt% to 0.05 wt%, Ti 0.01 wt% to 0.25 wt%, Mo 0.20 wt% to 0.40 wt%, Cr 0.30 wt% to 0.50 wt%, S ≤ 0.005 wt%, P ≤ 0.015 wt%, Alt 0.015 to 0.06 wt%, B 0.0008-0.0015%, with the remainder being Fe and unavoidable impurity elements.
[0025] Hot-rolled slabs are fed into a heating furnace at a temperature of ≥600℃ for gradient heating to obtain heated slabs. This application uses a furnace temperature above 600℃, which allows for direct heating using the slab's own residual heat, significantly shortening the overall furnace time, reducing furnace energy consumption, and improving production efficiency. Simultaneously, the higher initial slab temperature results in a smaller fundamental temperature difference between the furnace and the slab itself, leading to a more gradual heating rate between the slab surface and interior. This significantly reduces the differences in deformation due to thermal expansion and contraction, and also minimizes the problems of microstructure segregation and uneven oxidation caused by prolonged low-temperature residence when the slab is fed into the furnace at lower temperatures, ensuring the initial microstructure uniformity of the slab. Furthermore, if the slab is not fed into the furnace at a high temperature, there is a risk of breakage or cracking.
[0026] Meanwhile, the low-temperature furnace entry provides ample temperature control space for the three-stage heating. Due to the low furnace entry temperature, the heating process of the heating stage can be gradually advanced, ensuring that the preheating stage and the heating stage can gradually increase in temperature. This avoids the sudden growth of austenite grains when entering the furnace at high temperatures, creating conditions for grain refinement in the homogenization stage. In addition, it can also avoid energy waste caused by entering the furnace at high temperatures.
[0027] For example, the furnace temperature is 667°C, 652°C, 710°C, 819°C, 826°C, 836°C or any two of the above values.
[0028] In this embodiment of the application, a three-stage heating system is used in the heating furnace, including a preheating stage, a heating stage, and a soaking stage.
[0029] The preheating section is used to slowly heat up the slab, eliminating the temperature difference between the room temperature slab and the furnace, and avoiding thermal shock; the heating section is used to rapidly heat the slab to near the furnace exit temperature, achieving preliminary solid solution of alloying elements; the soaking section is used to homogenize the temperature of the slab, ensuring that the austenite grains are refined and uniform.
[0030] In some embodiments, the preheating section includes heating the slab to be heated to 800-1000°C at a rate of 0.05-0.15 min / °C.
[0031] After the slab enters the furnace, there is an initial temperature difference between the surface and the interior. If the heating rate is too fast, the surface heating rate will far exceed the internal heat conduction rate, leading to an exacerbation of the difference in deformation between surface expansion and internal contraction. This will cause the thermal stress to exceed the slab's tolerance limit, resulting in microcracks. A slow heating rate of 0.05-0.15 min / ℃ allows for gradual heat conduction within the slab, synchronizing the surface and interior heating rhythms. The temperature difference can be controlled within 30-50℃, keeping the thermal stress within a safe range and ensuring the structural integrity of the slab.
[0032] The slab contains microalloying elements such as Nb, V, and Ti, which easily trigger austenite grain growth at high temperatures. Although the preheating section does not reach the temperature at which austenite forms in large quantities, excessively rapid heating can cause a sudden temperature rise in local areas, prematurely forming a small number of coarse austenite grains that are difficult to refine later through the heating and soaking sections. A heating rate of 0.12-0.2 min / ℃ allows for a smooth temperature transition of the slab, avoiding local overheating and reserving microscopic conditions for the subsequent uniform refinement of austenite grains.
[0033] For example, the heating rate of the preheating section is 0.08 min / ℃, 0.10 min / ℃, 0.12 min / ℃, or any two of the above values.
[0034] The preheating section serves as a transitional stage, gradually raising the temperature to 800-1000℃. This allows the slab to gradually approach the high-temperature environment required for alloy solution treatment, avoiding uneven solution treatment caused by a rapid temperature jump from low to high in the heating section. The 800-1000℃ range can eliminate temperature differences and reserve heating space for the heating section to rapidly heat up to the furnace exit temperature. This achieves temperature uniformity without causing insufficient heating range due to excessively high target temperatures or increasing heating pressure due to excessively low temperatures.
[0035] The slab contains a significant amount of alloying material, and the core purpose of the heating section is to allow the microalloying elements to fully dissolve into the austenite. Preheating the slab to 800-1000℃ allows it to gradually approach the high-temperature environment required for alloy solution, avoiding uneven solution formation caused by a rapid temperature jump from low to high in the heating section. By allowing the slab to adapt to the medium-high temperature environment in the preheating section, the alloying elements can dissolve more smoothly into the austenite during the rapid heating, thus improving the solution-solving effect.
[0036] In some embodiments, the heating rate of the heating section is 0.12-0.20 min / ℃.
[0037] Microalloying elements such as Nb, V, and Ti in the slab need to be fully dissolved into austenite at high temperatures to lay the foundation for grain refinement in the soaking section and precipitation strengthening in the cooling section. A rapid heating rate of 0.12-0.20 min / ℃ can shorten the slab residence time in the high-temperature range: this avoids premature austenite grain growth due to slow heating and allows alloying elements to quickly enter the soaking section to complete solidification after the target temperature is reached, achieving rapid heating and sufficient solidification.
[0038] For example, the heating rate of the heating section is 0.12 min / ℃, 0.14 min / ℃, 0.15 min / ℃, 0.16 min / ℃, 0.18 min / ℃, 0.20 min / ℃, or a range between any two of the above values.
[0039] In some embodiments, the soaking time is 23-60 minutes.
[0040] Because multiple alloying elements are added to the slab, sufficient time is needed for the alloying elements to fully dissolve into the austenite, and at the same time, the austenite grains are transformed from uneven in size to uniform and fine. Therefore, the soaking time should be ≥23min. If the soaking time is insufficient, the grains will not be refined sufficiently, and the strength and toughness of the steel will fluctuate greatly after rolling, making it impossible to stably reach a tensile strength of ≥980MPa.
[0041] For example, the soaking time is 30 min, 45 min, 60 min, or any two of the above values.
[0042] The solid solution treatment of multi-element alloying elements such as Nb, V, and Ti in slabs requires relatively high temperatures. A temperature range of 1220-1260℃ ensures that these elements are fully dissolved into austenite, while simultaneously achieving uniform and refined austenite grains. If the furnace exit temperature is <1220℃, the alloy solid solution is insufficient, and the subsequent grain refinement and precipitation strengthening effects are significantly reduced. If the temperature is >1260℃, the austenite grains will grow excessively, making it difficult to refine them even during subsequent rolling, resulting in a significant decrease in the toughness of the steel.
[0043] For example, the furnace exit temperature is 1220°C, 1246°C, 1250°C, 1260°C, or any two of the above values.
[0044] In some embodiments, the total furnace time for the heating process is controlled to be 150-350 min.
[0045] The total furnace time is the synergistic guarantee of the three-stage heating. If the time is too short, the slab will not be heated thoroughly, the alloy will not be dissolved sufficiently, and the grain refinement will be uneven. If the time is too long, it will cause energy waste, increase production costs, and may also lead to excessive growth of austenite grains, which will reduce the final strength of the steel.
[0046] For example, the soaking time is 150 min, 200 min, 250 min, 300 min, 350 min, or any two of the above values.
[0047] In this embodiment, the iron oxide scale generated after the slab is heated is removed, and the slab is initially thinned by reasonable pass and temperature control, while maintaining the grain refinement trend, so as to reserve suitable thickness and temperature conditions for the finishing rolling process.
[0048] After the slab is heated, a layer of iron oxide scale (FeO, Fe2O3, etc.) will form on its surface. If it is not removed, it will be pressed into the surface of the steel during subsequent rolling, forming defects such as pitting and cracks, which seriously affect the surface quality of the steel and its subsequent processing performance.
[0049] In some embodiments, the pressure of the coarse descaling process is ≥18 MPa, which can ensure that the iron oxide scale is completely removed. The pressure design of this application can effectively improve the surface quality and meet the high requirements of commercial vehicle beams for surface precision.
[0050] In this embodiment, the roughing rolling process involves 5 or 7 passes. The selection of the number of passes needs to balance deformation uniformity and production efficiency. Too few passes will result in excessive deformation per pass, leading to stress concentration inside the slab and making it prone to cracking. Too many passes will increase the production cycle, reduce efficiency, and excessive deformation may cause uneven grain breakage. The design of 5 or 7 passes allows the slab to be gradually thinned, while deformation promotes the initial refinement of austenite grains.
[0051] The finishing temperature for rough rolling is 1080-1150℃. Excessive temperature leads to rapid austenite grain growth after rough rolling, making subsequent finishing rolling difficult and affecting the final strength. Insufficient temperature reduces the slab's plasticity, increases the load on the roughing mill, and increases the likelihood of rolling cracks. Simultaneously, this temperature allows for a reasonable cooling range at the finishing mill inlet temperature, preventing excessively high temperatures during finishing.
[0052] For example, the final rolling temperature is 1080°C, 1103°C, 1104°C, 1107°C, 1109°C, 1121°C, 1150°C or any two of the above values.
[0053] The intermediate slab thickness is 40-50mm. If the intermediate slab is too thin, multiple deformations are required during finish rolling to achieve a final thickness of 2.0-12.0mm, which can easily lead to surface hardening and dimensional inaccuracies in the steel. If it is too thick, the amount of deformation during finish rolling will be too large, increasing the load on the equipment and making it difficult to achieve uniform deformation, thus affecting the grain refinement effect. A thickness of 40-50mm allows for thinning within 3 or 5 passes during finish rolling, while fully utilizing the grain refinement and strengthening effect of finish rolling.
[0054] This application utilizes a heat insulation cover throughout the roughing rolling process. Because this application employs a heating regime of ≥600℃ for both furnace entry and exit, the overall temperature base of the slab is high. During roughing, the natural heat dissipation rate is rapid, easily leading to temperature differences between the slab surface, edges, and center, resulting in uneven temperature distribution. The heat insulation cover effectively blocks convective and radiative heat loss between the slab and the outside air, significantly reducing temperature loss during roughing, minimizing overall slab temperature fluctuations, and preventing problems such as uneven plasticity and inconsistent deformation caused by excessively rapid cooling and large temperature differences.
[0055] Meanwhile, using an insulation cover during rough rolling helps stabilize the inlet temperature within the range of 950-1080℃ during subsequent finish rolling. Without an insulation cover, the slab cools down too quickly, leading to a decrease in plasticity during finish rolling, which in turn affects surface quality and grain refinement.
[0056] In some embodiments, the use of a hot-rolled roll box for heat preservation and conveying of intermediate slabs is selected based on the rolling specifications.
[0057] Hot coil box is a key heat preservation equipment used in hot continuous rolling production line after roughing and before finishing. Its working principle is to roll the flat slab after roughing into a hot coil shape. By reducing the contact area between the slab and the air, the rate of radiative and convective heat dissipation is reduced, thus realizing the heat preservation and transportation of the slab from the roughing mill to the finishing mill.
[0058] The intermediate slab thickness is 40-50mm. After rough rolling, the temperature is 1080-1150℃ (RDT), while the finishing mill inlet temperature needs to be strictly controlled between 950-1080℃. If the temperature drops too quickly during transport, exceeding 100℃, it will lead to a decrease in slab plasticity and an increase in rolling force during finishing milling. Furthermore, it will be impossible to achieve "low-temperature rapid rolling" to reduce iron oxide scale, ultimately affecting grain refinement and surface quality. If the temperature drops insufficiently, remaining above 1080℃, it will violate the finishing mill inlet temperature limit, increasing the risk of oxidation. The hot coil box, through precise insulation, can control the slab temperature drop during transport within 30-50℃, ensuring the finishing mill inlet temperature remains stable within the target range, laying the foundation for subsequent processes.
[0059] In this embodiment of the application, precise temperature control and synchronous descaling are used in the finishing rolling stage to achieve a reduction in the final thickness of the slab, refine the grains, and improve the surface quality.
[0060] Finishing rolling often involves multiple passes, such as seven, and involves significant deformation. During the rolling process, the slab generates heat due to friction, and surface oxidation leads to the re-formation of iron oxide scale. If this scale is not removed promptly, it can cause surface defects in the final product. Descaling is used to remove newly formed iron oxide scale after each finishing rolling pass, while finishing descaling is used for the final removal of residual impurities.
[0061] In some embodiments, the descaling pressure of the fine descaling process is ≥18MPa: in conjunction with the coarse descaling pressure, it ensures that the iron oxide scale is completely removed during the fine rolling process, and the surface finish of the final product meets the processing requirements of commercial vehicle beams.
[0062] Commercial vehicle beams have extremely high requirements for surface quality. Under high-temperature environments, steel is prone to rapid oxidation, forming a thick layer of iron oxide scale that is difficult to completely remove through descaling. The finishing rolling entry temperature of this application, 950-1080℃, ensures sufficient plasticity in the steel to meet the requirements of finishing rolling deformation, while also shortening the steel's residence time in the high-temperature section, achieving low-temperature rapid rolling. This reduces the amount of iron oxide scale generated from the source, significantly improves surface quality, and lowers the risks of subsequent processing.
[0063] For example, the finishing mill inlet temperature is 950°C, 990°C, 1005°C, 1020°C, 1031°C, 1032°C, 1033°C, 1080°C or a range between any two of the above values.
[0064] At the finish rolling exit, the steel is in the deformed austenitic state. A finish rolling exit temperature (FDT) of 850-920℃ allows the grain boundaries or deformation bands of the deformed austenite to become the core nucleation sites for ferrite, forming a large number of fine ferrite grains with a grain size ≤10μm. According to the principle of fine grain strengthening, the finer the grains, the higher the strength and toughness of the steel. This is a crucial condition for achieving a tensile strength ≥980MPa and a Charpy impact energy ≥60J at -40℃. If the temperature is too high, the deformed austenite grains will grow, reducing the number of ferrite nuclei and resulting in coarse grains; if the temperature is too low, the transformation of deformed austenite into ferrite is too rapid, making it difficult to form a uniform and fine microstructure, thus reducing toughness.
[0065] For example, the outlet temperature is 850°C, 881°C, 885°C, 886°C, 888°C, 891°C, 893°C, 920°C or a range between any two of the above values.
[0066] In this embodiment, the cooling rate of the steel is precisely controlled to promote the full precipitation of microalloyed CN compounds, thereby achieving synergistic effects of fine grain strengthening and precipitation strengthening, while avoiding stress cracking caused by uneven cooling.
[0067] After finishing, the hot-rolled coil is at a high temperature of 850-920℃. At this temperature, the steel structure is deformed austenite. Rapid cooling is required to achieve two goals: first, to inhibit austenite grain growth and fix the fine deformed austenite structure; second, to create a suitable temperature range and cooling rhythm for microalloyed Nb, V, Ti, etc., to combine with C and N elements to form CN compounds. A single cooling mode is difficult to balance cooling rate and cooling uniformity. While ultra-fast cooling (UFC) can meet the speed requirements, it can easily lead to excessive temperature differences across the slab cross-section (faster cooling at the edges and slower cooling at the center), causing residual stress and surface cracks. Conventional segmented cooling alone results in insufficient cooling rate, which cannot inhibit austenite grain growth and leads to insufficient precipitation of CN compounds.
[0068] Therefore, this application designs a composite mode of ultra-fast cooling and front-end centralized cooling. Ultra-fast cooling (UFC) can rapidly reduce the temperature of steel, inhibit ferrite grain growth, and create conditions for the precipitation of microalloyed CN compounds (such as NbC, VC, TiC). Front-end centralized cooling involves applying cooling medium in the early stage of cooling to ensure uniform cooling of the steel cross-section and avoid stress concentration caused by excessive temperature difference between the edge and the center. If the cooling is uneven, it will cause warping and cracking of the steel during subsequent processing, which will not meet the requirements of laser cutting, bending and other processes.
[0069] In some embodiments, the number of ultra-fast cooling activation groups is 2 or 3. By adjusting the number of groups, the cooling rate can be controlled at 15-30℃ / s. This rate allows microalloying elements such as Nb, V, and Ti to combine with C and N to form fine CN compounds with a size ≤5nm. These precipitates can pin dislocations and hinder dislocation movement, further improving the strength of the steel without affecting its toughness. This is the key to achieving a balance between ultra-high strength and high toughness.
[0070] The coiling process can fix the microstructure of the steel, promote the full and uniform precipitation of microalloyed CN compounds, and at the same time realize the forming of the steel, which is convenient for storage and transportation.
[0071] After coiling, the steel will cool slowly in its coiled state. The temperature range of 520-580℃ provides sufficient time for the precipitation of CN compounds, ensuring a sufficient quantity and uniform distribution of precipitated phases, ultimately stabilizing the strength and toughness of the steel. If the coiling temperature is too high, the CN compounds will coarsen, weakening the precipitation strengthening effect and resulting in insufficient steel strength; if it is too low, the CN compounds will not precipitate sufficiently, and coiling the steel at low temperatures can easily generate residual stress, affecting subsequent processing performance.
[0072] For example, the winding temperature is 520°C, 526°C, 530°C, 536°C, 541°C, 543°C, 544°C, 580°C or a range between any two of the above values.
[0073] Coiling is not only a forming process, but it also allows the steel to maintain a uniform temperature in a coiled state, avoiding uneven structure during subsequent cooling. At the same time, the coiled shape can reduce secondary oxidation and scratches on the steel surface, further ensuring surface quality and providing a good foundation for subsequent processing of commercial vehicle beams, such as laser cutting, bending, and welding.
[0074] This application embodiment achieves product performance of 2.0-12.0mm thickness, tensile strength ≥980MPa, and Charpy impact energy ≥60J at -40℃ by comprehensively adjusting the hot rolling process chain and coordinating the parameters of each step, thus meeting the requirements of lightweighting and conventional processing technology for commercial vehicles.
[0075] Secondly, this application provides an ultra-high strength and toughness steel with a tensile strength ≥980MPa, which is prepared by the hot rolling production method of the first aspect of this application. The ultra-high strength and toughness steel has a thickness of 2.0-12.0mm, a tensile strength ≥980MPa, and a Charpy impact energy ≥60J at -40℃.
[0076] The ultra-high strength and toughness steel with a tensile strength ≥980MPa in this application embodiment can be used to manufacture longitudinal beams, cross beams and connecting plates for commercial vehicles, as well as I-beams for trailers. It is suitable for conventional processing techniques such as laser cutting, bending and welding, and meets the requirements for lightweighting of commercial vehicles.
[0077] Example The following embodiments describe the disclosure of this application in more detail. These embodiments are for illustrative purposes only, as various modifications and variations will be apparent to those skilled in the art within the scope of the disclosure of this application. Unless otherwise stated, all parts, percentages, and ratios reported in the following embodiments are based on mass, and all reagents used in the embodiments are commercially available or synthesized by conventional methods and can be used directly without further processing, and the instruments used in the embodiments are commercially available.
[0078] Example 1: A high-strength and high-toughness steel with a tensile strength ≥980MPa, the slab composition is as follows: C 0.1539wt%, Mn 1.2194wt%, Si 0.1411wt%, Nb 0.0219wt%, V 0.0355wt%, Ti 0.0172wt%, Mo 0.3673wt%, Cr 0.0304wt%, S 0.0014wt%, P 0.0093wt%, Alt 0.0303wt%, B 0.0010%, with the balance being Fe. The production method includes: Rolling thickness: 4.0mm Heating parameters: Furnace entry temperature 636℃, total furnace time 225min, furnace exit temperature 1245℃ The preheating section parameters are 860℃. The heating section parameters are 1280℃. The soaking section parameters are 1250℃.
[0079] Rolling temperatures: Roughing finishing temperature (RDT) 1121℃, Finishing entry temperature (FET) 1032℃, Finishing exit temperature (FDT) 891℃, Coiling temperature (CT) 544℃ Rolling process: The roughing process is carried out in 7 passes, and an insulation cover is used during the roughing process. The thickness of the intermediate billet is 41.07mm. The roughing descaling pressure is ≥18MPa, and the descaling is carried out in 5 passes. Two sets of ultra-fast cooling (UFC) are turned on, and the TMCP cooling mode is front-end concentrated.
[0080] Mechanical properties: Yield strength (ReL) 1010MPa, tensile strength (Rm) 1030MPa, elongation (A) 15.5%, Charpy impact energy (AK) at -40℃ is 156J, 154J, and 151J.
[0081] Example 2 A high-strength and high-toughness steel with a tensile strength ≥980MPa, the slab composition is as follows: C 0.1553wt%, Mn 1.2278wt%, Si 0.1537wt%, Nb 0.0239wt%, V 0.035wt%, Ti 0.019wt%, Mo 0.3172wt%, Cr 0.3233wt%, S 0.0010wt%, P 0.0107wt%, Alt 0.0406wt%, B 0.0011%, with the balance being Fe. The production method includes: Rolling thickness: 4.5mm Heating parameters: Furnace entry temperature 667℃, total furnace time 328min, furnace exit temperature 1246℃ The preheating section parameters are 878℃. The heating section parameters are 1267℃. The soaking section parameters are 1252℃.
[0082] Rolling temperatures: Roughing finishing temperature (RDT) 1109℃, Finishing entry temperature (FET) 990℃, Finishing exit temperature (FDT) 893℃, Coiling temperature (CT) 536℃ Rolling process: The roughing process is carried out in 7 passes, and an insulation cover is used during the roughing process. The thickness of the intermediate billet is 40.90mm. The roughing descaling pressure is ≥18MPa, and the descaling is carried out 5 times per pass. Two sets of ultra-fast cooling (UFC) are turned on, and the TMCP cooling mode is front-end centralized.
[0083] Mechanical properties: Yield strength (ReL) 1000MPa, tensile strength (Rm) 1020MPa, elongation (A) 14.5%, Charpy impact energy (AK) at -40℃ is 127J, 145J, and 136J.
[0084] Example 3 A high-strength and high-toughness steel with a tensile strength ≥980MPa, the slab composition is as follows: C 0.1599wt%, Mn 1.2344wt%, Si 0.1442wt%, Nb 0.0225wt%, V 0.0382wt%, Ti 0.0176wt%, Mo 0.3642wt%, Cr 0.3175wt%, S 0.0013wt%, P 0.0103wt%, Alt 0.0344wt%, B 0.0012%, with the balance being Fe. The production method includes: Rolling thickness: 5.0mm Heating parameters: Furnace entry temperature 610℃, total furnace time 261 min, furnace exit temperature 1250℃ The preheating section parameters are 942℃. The heating section parameters are 1309℃. The soaking section parameters are 1260℃.
[0085] Rolling temperatures: Roughing finishing temperature (RDT) 1103℃, Finishing entry temperature (FET) 1020℃, Finishing exit temperature (FDT) 888℃, Coiling temperature (CT) 530℃ Rolling process: Rough rolling adopts 5 passes, and heat preservation cover is used during the rough rolling process. The thickness of the intermediate billet is 44.80mm; the rough descaling pressure is ≥18MPa, and descaling is performed 3 times per pass; two sets of ultra-fast cooling (UFC) are turned on, and the TMCP cooling mode is front-end centralized.
[0086] Mechanical properties: Yield strength (ReL) 1040MPa, tensile strength (Rm) 1050MPa, elongation (A) 13.5%, Charpy impact energy (AK) at -40℃ is 148J, 134J, and 142J.
[0087] Example 4 A high-strength and high-toughness steel with a tensile strength ≥980MPa, the slab composition is as follows: C 0.1602wt%, Mn 1.2363wt%, Si 0.1377wt%, Nb 0.0234wt%, V 0.0382wt%, Ti 0.0203wt%, Mo 0.3559wt%, Cr 0.3227wt%, S 0.0015wt%, P 0.0081wt%, Alt 0.0351wt%, B 0.0011%, with the balance being Fe. The production method includes: Rolling thickness: 6.0mm Heating parameters: Furnace entry temperature 626℃, total furnace time 160min, furnace exit temperature 1250℃ The preheating section parameters are 894℃. The heating section parameters are 1298℃. The soaking section parameters are 1264℃.
[0088] Rolling temperatures: Roughing finishing temperature (RDT) 1104℃, Finishing entry temperature (FET) 1031℃, Finishing exit temperature (FDT) 886℃, Coiling temperature (CT) 543℃ Rolling process: Rough rolling adopts 5 passes, and heat preservation cover is used during the rough rolling process. The thickness of the intermediate billet is 45.59mm; the rough descaling pressure is ≥18MPa, and the descaling is performed 3 times per pass; two sets of ultra-fast cooling (UFC) are turned on, and the TMCP cooling mode is front-end centralized.
[0089] Mechanical properties: Yield strength (ReL) 1040MPa, tensile strength (Rm) 1060MPa, elongation (A) 15.5%, Charpy impact energy (AK) at -40℃ 136J, 132J, 138J Example 5 A high-strength and high-toughness steel with a tensile strength ≥980MPa, the slab composition is as follows: C 0.1666wt%, Mn 1.2261wt%, Si 0.1379wt%, Nb 0.0240wt%, V 0.0346wt%, Ti 0.0215wt%, Mo 0.3603wt%, Cr 0.3231wt%, S 0.0010wt%, P 0.0103wt%, Alt 0.0344wt%, B 0.0010%, with the balance being Fe. The production method includes: Rolling thickness: 8.0mm Heating parameters: Furnace entry temperature 619℃, total furnace time 261 min, furnace exit temperature 1250℃ The preheating section parameters are 885℃. The heating section parameters are 1293℃. The soaking section parameters are 1255℃.
[0090] Rolling temperatures: Roughing finishing temperature (RDT) 1107℃, Finishing entry temperature (FET) 1033℃, Finishing exit temperature (FDT) 885℃, Coiling temperature (CT) 541℃ Rolling process: Rough rolling adopts 5 passes, and heat preservation cover is used during the rough rolling process. The thickness of the intermediate billet is 48.28mm; the rough descaling pressure is ≥18MPa, and descaling is performed 3 times per pass; 3 sets of ultra-fast cooling (UFC) are turned on, and the TMCP cooling mode is front-end concentrated.
[0091] Mechanical properties: Yield strength (ReL) 1030MPa, tensile strength (Rm) 1050MPa, elongation (A) 14.0%, Charpy impact energy (AK) at -40℃ 135J, 129J, 127J Example 6 A high-strength and high-toughness steel with a tensile strength ≥980MPa, the slab composition is as follows: C 0.1571wt%, Mn 1.2292wt%, Si 0.1369wt%, Nb 0.0232wt%, V 0.0375wt%, Ti 0.022wt%, Mo 0.3692wt%, Cr 0.3203wt%, S 0.0008wt%, P 0.0085wt%, Alt 0.0330wt%, B 0.0012%, with the balance being Fe. The production method includes: Rolling thickness: 10.0 mm Heating parameters: Furnace entry temperature 652℃, total furnace time 197min, furnace exit temperature 1248℃ The preheating section has a temperature of 987℃, the heating section has a temperature of 1294℃, and the soaking section has a temperature of 1258℃.
[0092] Rolling temperatures: Roughing finishing temperature (RDT) 1103℃, Finishing entry temperature (FET) 1005℃, Finishing exit temperature (FDT) 881℃, Coiling temperature (CT) 526℃ Rolling process: Rough rolling adopts 5 passes, and heat preservation cover is used during the rough rolling process. The thickness of the intermediate billet is 49.54mm; the rough descaling pressure is ≥18MPa, and descaling is performed 3 times per pass; 3 sets of ultra-fast cooling (UFC) are turned on, and the TMCP cooling mode is front-end centralized.
[0093] Mechanical properties: Yield strength (ReL) 1020MPa, tensile strength (Rm) 1030MPa, elongation (A) 16.0%, Charpy impact energy (AK) at -40℃ 197J, 177J, 198J.
[0094] Comparative Example 1 A type of steel, with the same slab composition and production method as in Example 3, differing in that: The slab temperature upon entering the furnace is 420℃.
[0095] Product characteristics: After the slab is put into the furnace at a low temperature, the temperature difference between the furnace temperature and the slab temperature is large. The long-term low-temperature residence leads to local segregation of the slab structure and slight uneven oxidation. The overall heating time in the furnace is forced to be extended, and the energy consumption is significantly increased. The mechanical properties of the finished product fluctuate greatly, with an average tensile strength of 960MPa.
[0096] Comparative Example 2 A type of steel, with the same slab composition as in Example 3 and a similar production method as in Example 3, except that the soaking time is adjusted to 20 minutes, while all other parameters remain unchanged.
[0097] Product characterization: Insufficient solid solution of multi-element microalloying elements, and uneven austenite grain size; Mechanical properties: tensile strength 945 MPa, average Charpy impact energy at -40℃ 52 J; insufficient soaking time leads to poor alloy solution treatment and grain refinement, failing to meet strength and low-temperature toughness requirements. Comparative Example 3 A type of steel, with the same slab composition and production method as in Example 3, except that the insulation cover for the rough rolling process is omitted.
[0098] Test results: The temperature drop exceeded the standard during the process of conveying the slab from the rough rolling mill to the finishing mill. The temperature drop at the edge and surface of the slab was much faster than that at the center, resulting in uneven plasticity distribution. The finishing mill inlet temperature (FET) dropped to 920℃. The finishing mill rolling force increased, the plate deformation was uneven, and the grain refinement effect deteriorated. The finished product had a tensile strength of 950MPa and an average Charpy impact energy of 55J at -40℃. Both the strength and low-temperature toughness did not meet the standards, and there were slight rolling texture defects on the plate surface.
[0099] Comparative Example 4 A type of steel, the slab composition is the same as that of Example 3, and the production method is similar to that of Example 3, except that the slab exit temperature is adjusted to 1200℃.
[0100] Experimental results: Under high-temperature furnace conditions, the excessively low furnace exit temperature cannot meet the solid solution temperature requirements of multi-element microalloying elements. The solid solution of Nb and Ti carbonitrides is incomplete, and the amount and size of the strengthening phase precipitated during the subsequent cooling process are insufficient. The austenite refinement is insufficient, and the overall grain size is too coarse. The tensile strength of the finished product is 920 MPa, and the low-temperature impact energy is significantly reduced, failing to meet the ultra-high strength and toughness steel index.
[0101] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of this application, and are not intended to limit them. Although this application has been described in detail with reference to the foregoing embodiments, those skilled in the art should understand that modifications can still be made to the technical solutions described in the foregoing embodiments, or equivalent substitutions can be made to some or all of the technical features therein. Such modifications or substitutions do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of this application.
Claims
1. A hot-rolling production method for ultra-high strength and toughness steel with a tensile strength ≥980MPa, characterized in that, Includes the following steps: Obtain the hot-rolled slab; The hot-rolled slab is fed into a heating furnace at a temperature of ≥600℃ to heat the slab and obtain a heated slab; wherein the heating process includes a preheating section, a heating section and a soaking section, the soaking section time is controlled to be ≥30min, and the furnace exit temperature is 1220-1260℃. After rough descaling, the heated slab is rough rolled to obtain an intermediate slab; wherein the rough rolling is performed in 5 or 7 passes, the final rolling temperature of the rough rolling is 1080-1150℃, a heat insulation cover is used during the rough rolling process, and the thickness of the intermediate slab is 40-50mm. The intermediate slab is precision rolled to obtain a hot-rolled coil; during the precision rolling process, a fine descaling treatment is performed simultaneously. The finishing mill inlet temperature is 950-1080℃, and the finishing mill outlet temperature is 850-920℃. The hot-rolled coil is cooled using an ultra-fast cooling and front-end centralized cooling mode to obtain the hot-rolled finished product; The hot-rolled product is coiled to obtain the ultra-high strength and toughness steel, and the coiling temperature is 520-580℃.
2. The production method according to claim 1, characterized in that, The total furnace time for the heating process is controlled to be 150-350 min.
3. The production method according to claim 1 or 2, characterized in that, The preheating section includes heating the slab to be heated to 800-1000℃ at a rate of 0.05-0.15 min / ℃. The heating rate of the heating section is 0.12-0.20 min / ℃; The soaking time is 23-60 minutes.
4. The production method according to claim 1, characterized in that, The pressure for both the coarse descaling and fine descaling processes is ≥18 MPa.
5. The production method according to claim 1, characterized in that, Whether to use a hot-rolling box to keep the intermediate slab warm during transport depends on the rolling specifications.
6. The production method according to claim 1, characterized in that, The hot-rolled slab comprises the following components by mass fraction: C 0.15wt%~0.17wt%, Mn 1.15wt%~1.35wt%, Si 0.10wt%~0.25wt%, Nb 0.02wt%~0.04wt%, V 0.03wt%~0.05wt%, Ti 0.01wt%~0.25wt%, Mo 0.20wt%~0.40wt%, Cr 0.30wt%~0.50wt%, S≤0.005wt%, P≤0.015wt%, Alt 0.015~0.06wt%, B 0.0008-0.0015%, with the remainder being Fe and unavoidable impurity elements.
7. The production method according to claim 1, characterized in that, The ultra-high strength and toughness steel has a thickness of 2.0-12.0 mm and a Charpy impact energy of ≥60 J at -40℃.
8. A high-strength and high-toughness steel with a tensile strength ≥980MPa, characterized in that, The ultra-high strength and toughness steel is prepared by any one of the production methods described in claims 1-7, and has a thickness of 2.0-12.0 mm, a tensile strength ≥980 MPa, and a Charpy impact energy ≥60 J at -40℃.